PERAN DAN FUNGSI PEJABAT PENGAWAS PENYIDIK POLRI DALAM PENGAWASAN INTERNAL TERKAIT TERJADINYA MALADMINISTRASI DALAM PROSES PENYIDIKAN (Studi di Polresta Pontianak Kota) - MOCHAMAD NU'AIM QOMARUDIN,SH. A.21211100, Jurnal Mahasiswa S2 UNTAN (Jurnal NESTOR Magister Hukum, 2014)
ABSTRACTIndonesian National Police has the main task of maintaining security and public order, enforce the law and provide protection, guidance and service to the community. In the criminal law enforcement process, always followed by a process of orderly administration. Investigation is an administrative violation act of maladministration. The practice of maladministration in the process of investigation in Pontianak City Police, generally occurs in the form of a protracted settlement, misuse of authority, eliminating evidence, partisanship and not according to the procedure in handling cases. To Prevent maladministration practice , it would require close supervision and effective in the process of investigations conducted by the investigator and officer bearers boss supervision . An indicator function has not been effective when the oversight was discovered irregularities , the which is Characterized by disappointment and complaints from the public. Such conditions , can cause unfavorable image of the performance of the police force Police.In analyzing the subject matter, the study carried out by the method of descriptive analysis of socio-legal approach. Consideration of the choice of methods and approaches, is expected to explain the phenomenon of the working of the law relating to aspects of the practice of surveillance and investigation of maladministration in the process of becoming more comprehensive and in-depth.The findings of the research, the investigation showed that the practice of maladministration in Pontianak City Police occurred because of an oversight in the investigation process is not optimal, several factors including the mental factors of law enforcement, the legal factor itself, the lack of officer bearers factor surveillance functions of investigation and sanction of an investigating factors that convicted of violations in the investigation process. Therefore, the police are expected to make efforts to optimize the supervision of the investigation process by increasing the number of official investigations supervisor, impose strict sanctions against the investigator and the investigator supervisory officials who are convicted of the offense, increase the ability of the investigator and the investigator supervising official regulations related to the understanding and implementation legislation through education programs and increased professional development.Keywords : maladministration, Investigations, Oversight and Police.